Perceptions of Exercise Interventions in Pregnancy; A Cross Sectional Survey of Health Care Workers in Kaduna State - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The potential benefits of exercise to pregnant women and their unborn children are immense, yet regular exercise prescription may not be the norm.Aims:Our study aimed to investigate the perceptions and practices of obstetric care providers regarding exercise in pregnancy.Materials and Methods:The study was a cross-sectional survey done in Kaduna state between July and December 2020. A pretested questionnaire was given to obstetric care providers and information was obtained about demographics, professional and facility characteristics of respondents, their perceptions, and practices related to exercise in pregnancy, and information they routinely give pregnant women regarding exercise. Descriptive analysis was done using frequencies, percentages, mean, and standard deviation.Results:There were 265 respondents with a mean age of 34.23 ± 9.29 years. They were mostly females (215, 82.1%), married (171, 65.3%), Muslim (137, 52.3%), and Hausa (107, 40.8%). There were more nurses (153, 58.4%) from the public (212, 80.9%) and tertiary (133, 50.8%) health facilities. Almost all respondents agreed that exercise during pregnancy was beneficial (258, 98.5%). The commonest indication for exercise was cited as obesity and diabetes, whereas it was mostly contraindicated with bleeding while pregnant. The commonest barriers to exercise in pregnancy were the fear of pregnancy complications, inadequate knowledge, and high workload.Conclusion:Healthcare workers in this study generally had positive perceptions and practices toward exercise during pregnancy, except for the fact that they feel pregnant women should avoid strength-building exercises, and do not usually recommend individualized programs. Local guidelines need to be developed for EIP and providers better trained.